Pemanfaatan DNA barcoding untuk ketertelusuran label berbagai produk olahan ikan berbasis surimi komersial - Asadatun Abdullah; Hana Aulia Sativa; Tati Nurhayati; Mala Nurilmala (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
Surimi-based processed products are prone to mislabeling using raw materials that are not in accordance with food safety requirements. There were cases reporting use of toxic fish tissue in commercial seafood products. This study was aimed to identify and determine the raw materials used in various processed surimi products using cytochrome oxidase I (COI) gene marker. The experiment consisted of DNA isolation, DNA amplification using several target primers namely full-length barcodes, mini-barcodes, as well as specific species primers against poisonous puffer fish Lagocephalus lunaris and genetic analysis. The results of bioinformatics analysis revealed that S1 samples were Coryphaena hippurus or mahi-mahi fish, S2 and S3 samples were Nemipterus bathybius or curated fish and CS samples were Evynnis cardinalis or kuro fish. Detection of samples with species specific primers of puffer fish Lagocephalus lunaris with annealing temperatures of 54°C, 57°C, and 60°C showed no DNA bands in the six samples analyzed.